1999
DOI: 10.1046/j.1440-1746.1999.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and differentiation of the human colon carcinoma cell line, Caco‐2, by constitutive expression of insulin‐like growth factor binding protein‐3

Abstract: The human colon carcinoma cell line, Caco-2, produces insulin-like growth factor binding protein-3 (IGFBP-3), the secretion of which correlates with markers of enterocyte differentiation. To investigate whether IGFBP-3 inhibits proliferation or induces differentiation, Caco-2 cells were stably transfected with an IGFBP-3 cDNA expression construct or pcDNA3 vector as a control. Accumulation of IGFBP-3 mRNA and secretion of the protein into conditioned medium 9 days after plating were readily detected in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The involvement of IGFBP-3 in the inhibition of cell growth is evident when human IGFBP-3 cDNA is transfected into mammalian cell lines like colon cancer cells (MacDonald et al, 1999), human breast cells (Firth et al, 1998a) and mouse fibroblast cells (Cohen et al, 1993). Apoptosis inducing effect of IGFBP-3 has been demonstrated to be an IGF-dependent as well as an IGF-independent process.…”
Section: Igf-independent Role Of Igfbp-3 In Apoptosismentioning
confidence: 99%
“…The involvement of IGFBP-3 in the inhibition of cell growth is evident when human IGFBP-3 cDNA is transfected into mammalian cell lines like colon cancer cells (MacDonald et al, 1999), human breast cells (Firth et al, 1998a) and mouse fibroblast cells (Cohen et al, 1993). Apoptosis inducing effect of IGFBP-3 has been demonstrated to be an IGF-dependent as well as an IGF-independent process.…”
Section: Igf-independent Role Of Igfbp-3 In Apoptosismentioning
confidence: 99%
“…More IGF can become bioavailable to stimulate the IGF-1R due to diminished IGFBP sequestration; this may be achieved by either reduced IGFBP production and/or by increased IGFBP proteolysis. For example, when Caco-2 human colon carcinoma cells were stably transfected with an IGFBP-3 cDNA expression construct, they achieved a much lower final cell density after one-and-a-half weeks of growth and began transcription of sucrase-isomaltase, a marker of enterocyte differentiation; in Caco-2 cells transfected with empty plasmid, IGFBP-3 was undetectable, growth was unimpaired, and sucrase-isomaltase was not produced (MacDonald et al, 1999). Increased proteolysis of IGFBP-3 has been shown in prostate cancer by PSA (Cohen et al, 1992), cathepsin D (Nunn et al, 1997), urokinase and plasminogen-activator (Angelloz-Nicoud and Binoux, 1995).…”
Section: Igfs and Igfbps In Carcinogenesismentioning
confidence: 99%
“…Macdonald et al (90) in 1999 demonstrated that the human colon carcinoma cell line, Caco-2, which was stably transfected with an IGFBP-3 expression construct, grew more slowly in vitro than the cells transfected with a control vector.…”
Section: Igf-ii Expressionmentioning
confidence: 99%